2020
DOI: 10.1080/09658211.2020.1828476
|View full text |Cite
|
Sign up to set email alerts
|

Czech and Slovak life scripts: the rare case of two countries that used to be one

Abstract: In this study, we examined cultural life scripts in two countries, the Czech Republic and Slovakia. The cultural life script is semantic knowledge about culturally shared expectations regarding the order and timing of important life events during an idealized life course. For many decades, Slovakia and the Czech Republic were one country: Czechoslovakia. After a regime change in 1989 and the separation of the Czech Republic and Slovakia in 1993, their two cultures have been evolving and changing independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The Newborn life script contained 46 life events, a rather large number. As in cultural life scripts from other countries (Štěpánková et al, 2020), many events referred to social and educational life events, and to lesser extents to religious customs. Similar to the Qatari Newborn life script (Ottsen & Berntsen, 2014), the Emirati Newborn life script included the religious events gender‐congruent activities and expectations, learning Quran and Islamic teachings , and Islamic birth rituals .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Newborn life script contained 46 life events, a rather large number. As in cultural life scripts from other countries (Štěpánková et al, 2020), many events referred to social and educational life events, and to lesser extents to religious customs. Similar to the Qatari Newborn life script (Ottsen & Berntsen, 2014), the Emirati Newborn life script included the religious events gender‐congruent activities and expectations, learning Quran and Islamic teachings , and Islamic birth rituals .…”
Section: Discussionmentioning
confidence: 99%
“…Research has obtained cultural life scripts in Australia, China, the Czech Republic, Denmark, Germany, Greenland, Japan, Malaysia, Mexico, the Netherlands, Portugal, Qatar, Slovakia, Turkey, and the United States (Berntsen & Rubin, 2004; Bohn, 2010; Bohn & Bundgaard‐Nielsen, 2021; Erdoğan et al, 2008; Habermas, 2007; Hatiboğlu & Habermas, 2016; Janssen et al, 2014; Janssen & Haque, 2018; Janssen & Rubin, 2011; Kawasaki & Uehara, 2020; Ottsen & Berntsen, 2014; Özbek et al, 2021; Rubin et al, 2009; Saraiva et al, 2021; Štěpánková et al, 2020; Tekcan et al, 2012; Zaragoza Scherman et al, 2017). All studies found that life scripts were mostly positive and referred to socially important events of educational, family, and occupational life similar in most countries, as well as to culturally specific, partly religious events unique to individual countries.…”
Section: Characteristics Of Cultural Life Scriptsmentioning
confidence: 99%
“…Despite cultural life scripts being predominantly positive, death and illness are mentioned as expected life events across a wide range of cultures (e.g. Berntsen & Rubin, 2004;Bohn, 2010;Hatiboğlu & Habermas, 2016;Janssen, Uemiya, & Naka, 2014;Ottsen & Berntsen, 2014;Rubin, Berntsen, & Hutson, 2009;Zaragoza Scherman, Salgado, Shao, & Berntsen, 2017), whereas accidents are rarely mentioned in life scripts, and disasters not at all (Coleman, 2014;Erdoğan, Baran, Avlar, Taş, & Tekcan, 2008;Janssen & Haque, 2018;Janssen & Rubin, 2011;Štěpánková, Kadlčíková, & Zaragoza Scherman, 2020). Hence, not only are deaths and illnesses serious and potentially traumatic events, they are also relatively common, to some extent expected, and considered important in a cultural context.…”
Section: Discussionmentioning
confidence: 99%
“…Because the experiences and expectations in life vary across cultures, several researchers have examined the cross‐cultural stability of life scripts. Toward that end, cross‐cultural studies of the cultural life script have been conducted between distinct nationalities, such as Denmark and the United States (Rubin et al, 2009), China, Denmark, Greenland, and Mexico (Zaragoza Scherman et al, 2015), Germany and Turkey (Hatiboğlu & Habermas, 2016), Australia and Malaysia (Janssen & Haque, 2018), and the Czech Republic and Slovakia (Štěpánková et al, 2020). In addition, studies examining the cultural life script with single samples have included nationalities such as Denmark (Berntsen & Rubin, 2004), Japan (Janssen et al, 2014; Kawasaki & Uehara, 2020), and the Netherlands (Janssen & Rubin, 2011).…”
Section: Cultural Life Scriptsmentioning
confidence: 99%